Thrombopoietin Receptor Agonist Mitigates Hematopoietic Radiation Syndrome and Improves Survival after Whole-Body Ionizing Irradiation Followed by Wound Trauma - Juliann G. Kiang; Min Zhai; Pei-Jun Liao; Connie Ho; Nikolai V. Gorbunov; Thomas B. Elliott (Mediators of Inflammation)
Ionizing radiation combined with trauma tissue injury (combined injury, CI) results in greater mortality and H-ARS than radiation alone (radiation injury, RI), which includes thrombocytopenia. The aim of this study was to determine whether increases in numbers of thrombocytes would improve survival and mitigate H-ARS after CI. We observed in mice that WBC and platelets remained very low in surviving RI animals that were given 9.5 Gy 60Co-γ-photon radiation, whereas only lymphocytes and basophils remained low in surviving CI mice that were irradiated and then given skin wounds. Numbers of RBC and platelets, hemoglobin concentrations, and hematocrit values remained low in surviving RI and CI mice. CI induced 30-day mortality higher than RI. Radiation delayed wound healing by approximately 14 days. Treatment with a thrombopoietin receptor agonist, Alxn4100TPO, after CI improved survival, mitigated body-weight loss, and reduced water consumption. Though this therapy delayed wound-healing rate more than in vehicle groups, it greatly increased numbers of platelets in sham, wounded, RI, and CI mice; it significantly mitigated decreases in WBC, spleen weights, and splenocytes in CI mice and decreases in RBC, hemoglobin, hematocrit values, and splenocytes and splenomegaly in RI mice. The results suggest that Alxn4100TPO is effective in mitigating CI.